Analisis Pelaksanaan Program Uks Terhadap Perilaku Hidup Bersih Dan Sehat Siswa - Susi Susanti; Ayatullah; A Rizki Awan (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
This study aims to analyze the relationship between the implementation of the School Health Program (UKS) and Clean and Healthy Living Behavior (PHBS) at SMP Negeri 05 Tamalatea. The research method used is quantitative with a cross-sectional design, involving 84 students selected using the purposive sampling technique. Data was collected through a questionnaire tested for validity and reliability, then analyzed using the chi-square test. The results show a significant relationship between the implementation of the UKS program and students' PHBS (p-value = 0.004), indicating that the better the implementation of the UKS program, the higher the students' awareness in practicing PHBS. However, some challenges were found in the program implementation, such as the lack of active involvement of students and educators in UKS activities. Therefore, strengthening education and implementing the UKS program effectively is necessary to enhance its role in shaping healthy living behaviors in the school environment.